Thermal tolerance and the potential effects of climate change on coastal intertidal and estuarine organisms in the Kariega Estuary and adjacent intertitdal coastline, Eastern Cape, South Africa - Van der Walt, Kerry-Ann (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Temperature changes due to the effects of climate change are evident on all continents and oceans. As a result, there is a growing concern over how marine ectotherms will respond to extreme or fluctuating environmental temperatures. Temperature changes have strong direct and indirect effects on individual, population, and ecosystem functioning traits. A multi-scale approach determining the thermal tolerance and performance of several marine ectotherms belonging to different coastal habitats is rarely considered in thermal physiology studies but is effective for an integrated ecosystem assessment. As such, for this thesis, I aimed to quantify and compare the thermal tolerance and performance of a range of coastal marine ectotherms (fish and macro-invertebrates) with different biogeographical distributions from estuarine, subtidal and rocky intertidal habitats to available and projected in situ temperature data. This was also undertaken to gauge the local vulnerability of each species across summer and winter in a warm-temperate region of South Africa. This was done using a multi-method physiological approach, which included the dynamic method (CTmax and CTmin), static respirometry and maximum heart rate fHmax). Results of the dynamic method on several fish and macro-invertebrate species indicated that there are differences in thermal tolerance according to taxonomy, biogeography and habitat for both summer and winter. Macro-invertebrate species generally had higher CTmax endpoints, lower CTmin endpoints, higher upper and lower breadths in tolerance, higher upper and lower thermal safety margins and higher thermal scopes than the fish species. This could be a result of the macro-invertebrate species studied being less mobile compared with fish species (which are able to move to more favourable conditions) as well as having broader geographical distributions. In addition, macro-invertebrates from the intertidal rock pool habitat (Palaemon peringueyi; Pernaperna) were more tolerant of high and low temperatures compared with the macro-invertebrates from the estuarine habitat (Clibanarius virescens; Parasesarma catenatum; Upogebia africana). Overall, macro-invertebrates, with the exception of Parechinus angulosus, investigated in this study indicated that current temperatures and projected climate change scenarios across seasons would not have a significant impact on them and that they are highly adaptable to changing temperature regimes. This sign of high tolerance was further supported by the heart rates of P. perna and P. catenatum under an acute increase in temperature (1.0 °C.h-1) which showed individuals of each species physiologically depressing their metabolism until a final Arrhenius breakpoint temperature was reached (TAB). Among the fish species investigated in this study, tropical species (Chaetodon marleyi; Kuhlia mugil) had the highest CTmax and CTmin endpoints when compared with the temperate (Diplodus capensis; Sarpa salpa), warm-water endemic (Chelon dumerili; Rhabdosargus holubi) and cool-water endemic (Chelon richardsonii) fishes. This suggests that due to their lower breadths in tolerance and thermal safety margins being small, tropical species may be less tolerant of cold temperatures and thermal variability, especially in the form of summer upwelling events which are expected to increase in intensity and frequency in this region as a result of anthropogenic climate change effects. On the other hand, however, if a temperature increase of 2.0 - 4.0 °C takes place at the end of the century as predicted by the Intergovernmental Panel on Climate Change (IPCC), it is likely that tropical species such as C. marleyi will become more common. Temperate species such as D. capensis and S. salpa were able to tolerate a wide range of temperatures (wide thermal scope) compared with the other fish species. These findings may suggest that D. capensis and S. salpa are thermally resilient and may be the least vulnerable to climate change effects and temperature variability. When evaluating the different life stages of D. capensis, however, using the dynamic method (juveniles and adults), static respirometry (juveniles) and maximum heart rate (adults), results suggested that juveniles of this temperate species will be more resilient to increases in ocean temperatures compared with the adults because they have a higher thermal tolerance (CTmax/TCRIT) and a greater metabolic scope (TOPT) at higher temperatures. For both juveniles and adults, temperatures beyond 28.0 °C (upper Tpej; Tarr) will have a significant impact on their physiology. Using a multi-scale and multi-method approach thus helped to identify which species or community may be vulnerable to the effects of climate change within shallow coastal environments in this warm-temperate climate change hotspot. Adopting this type of approach will assist policy makers in developing comprehensive climate change management frameworks for coastal ecosystems globally and around South Africa.
Keywords: Ectotherms -- Climatic factors; Ectotherms -- Effect of temperature on; Fishes -- Climatic factors; Fishes -- Effect of temperature on; Climatic changes -- South Africa -- Eastern Cape